Outcome predictors of influenza for hospitalization and mortality in children. Issue 11 (9th February 2021) - Ozsurekci, Yasemin; Aykac, Kubra; Bal, Fatma; Bayhan, Cihangul; Basaranoglu, Sevgen T.; Alp, Alpaslan; Cengiz, Ali Bulent; Kara, Ates; Ceyhan, Mehmet
Abstract: Severity of disease caused by influenza virus and the influencing factors that may be different. Moreover, the disease course actually may not be determined specifically in children because of lower seroprotection rates of children. Herein, the results clinic and outcome data of children with influenza from Turkey were reported. We present here the results from 2013 to 2017. Nasopharyngeal swab samples of the children with influenza were investigated via multiplex polymerase chain reaction. A total of 348 children were diagnosed with influenza; 143 (41.1%) were influenza A, 85 (24.4%) were influenza B, and 120 (34.5%) were mixt infection with other respiratory viruses. Fifty‐four percent of children admitted to intensive care unit (ICU) were under 2 years of age ( p = .001). Having an underlying disease was detected as the main predictor for both hospitalization and ICU stay according to multiple logistic regression analysis (odds ratio [OR], 11.784: 95% confidence interval [CI], 5.212–26.643; p = .001 and OR, 4.972: 95% CI, 2.331–10.605; p = .001, respectively). Neurological symptoms most frequently seen in cases who died (44.4%; p = .02). Lymphopenia was relatively higher (55.6%) and thrombocytopenia was most frequently seen in cases who died (77.8%) with a significant ratio ( p = .001). Underlying diseases was found a risk factor for influenza being hospitalized and being admitted to ICU. Children under 2 years of age and with underlying diseases should be vaccinated particularly in countries where the influenza vaccination is still not routinely implemented in the immunization schedule. Highlights Underlying diseases is a risk factor for influenza to be hospitalized and admitted to ICU. Influenza vaccination is of great importance to prevent life‐threatening complications of influenza, particularly in children require ICU admission. The possibility to reduce the outpatient visit number by vaccination has a great impact on disease burden in addition to the underestimated crucial social benefits, as well.